2011
DOI: 10.1002/bjs.7620
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of screening for abdominal aortic aneurysm in the Netherlands and Norway

Abstract: Using this model, screening for AAA in 65-year-old men would be highly cost-effective in both the Netherlands and Norway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 61 publications
2
29
0
1
Order By: Relevance
“…76,78,79,100,101 Economic models that use age-specific population norms report values in the range 0.72-0.87. 80,[95][96][97][98]102,103 In all but one study 96 the values were derived from the European Quality of Life-5 Dimensions (EQ-5D). Table 34 reports the probability data used to estimate weighted average costs for those patients with a ruptured AAA and for the perioperative and postoperative costs of elective AAA repair and Tables 57 and 58 in Appendix 12 report the cost of events used in the economic model for the primary and sensitivity analyses.…”
Section: Economic Evaluation: Data Inputs and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…76,78,79,100,101 Economic models that use age-specific population norms report values in the range 0.72-0.87. 80,[95][96][97][98]102,103 In all but one study 96 the values were derived from the European Quality of Life-5 Dimensions (EQ-5D). Table 34 reports the probability data used to estimate weighted average costs for those patients with a ruptured AAA and for the perioperative and postoperative costs of elective AAA repair and Tables 57 and 58 in Appendix 12 report the cost of events used in the economic model for the primary and sensitivity analyses.…”
Section: Economic Evaluation: Data Inputs and Resultsmentioning
confidence: 99%
“…76,78,79,100,101 The approach used in this evaluation is similar to that used in evaluations of the cost-effectiveness of screening and surveillance programmes for AAA. 80,[95][96][97][98]102,103 However, there are a number of limitations. The first is that published population norms aggregated utility values for age ranges, rather than by year of age.…”
Section: Economic Analysismentioning
confidence: 99%
“…A systematic review of the models to 2006 emphasised the variability in their estimates of cost-effectiveness. 57 Since that review, a number of further modelling studies have been published drawing on data from a variety of sources: for example studies relating to Italy, 15 to the Netherlands and Norway, 58 to Canada 59,60 and to Denmark. 61 These have all concluded that screening is acceptably cost-effective, with the exception of a study using data from Denmark and other sources, which concluded that screening did not seem to be cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48] AAA screening was cost effective, with an incremental cost-efficiency ratio of less than US$30 000 per qualityadjusted life-year gained. 22 A recent report on outcomes of the Swedish nationwide screening program concluded that screening for AAA remains cost effective, despite declining prevalence and a shift to more expensive procedures.…”
Section: Resource Usementioning
confidence: 99%